A CMOS quadrature VCO with optimized Colpitts topology for low-voltage applications. (February 2018) - Hemmati, Mohammad Jafar; Hakimi, Ahmad
Abstract: In this work, a new configuration of differential drain-to-source Colpitts LC voltage controlled oscillator (VCO) is proposed for low voltage applications. The circuit employs two capacitors in a cross-coupled positive feedback to separate the gate biasing of switching transistors from their drain dc voltages. This technique provides lower overdrive voltage for switching transistors which reduces the needing supply voltage. Besides, another positive feedback is imposed in this configuration which decreases the required transconductance for start-up oscillation. Also, a new quadrature VCO (QVCO) is presented by realizing two identical prior proposed Colpitts VCOs. The coupling technique used in the proposed QVCO improves the phase noise performance of the circuit. A linear analysis is presented to confirm that the oscillator can generate outputs with 90° phase difference. Additionally, the Monte Carlo (MC) simulation is performed to estimate the accuracy of the proposed circuit performance under various device mismatches.